Combined Use of Cultivation-Dependent and Cultivation-Independent Methods Indicates that Members of Most Haloarchaeal Groups in an Australian Crystallizer Pond Are Cultivable - Burns, D. G. (American Society for Microbiology, 2004)
Haloarchaea are the dominant microbial flora in hypersaline waters with near-saturating salt levels. The haloarchaeal diversity of an Australian saltern crystallizer pond was examined by use of a library of PCR-amplified 16S rRNA genes and by cultivation. High viable counts (10(6) CFU/ml) were obtained on solid media. Long incubation times (≥8 weeks) appeared to be more important than the medium composition for maximizing viable counts and diversity. Of 66 isolates examined, all belonged to the family Halobacteriaceae, including members related to species of the genera Haloferax, Halorubrum, and Natronomonas. In addition, isolates belonging to a novel group (the ADL group), previously detected only as 16S rRNA genes in an Antarctic hypersaline lake (Deep Lake), were cultivated for the first time. The 16S rRNA gene library identified the following five main groups: Halorubrum groups 1 and 2 (49%), the SHOW (square haloarchaea of Walsby) group (33%), the ADL group (16%), and the Natronomonas group (2%). There were two significant differences between the organisms detected in cultivation and 16S rRNA sequence results. Firstly, Haloferax spp. were frequently isolated on plates (15% of all isolates) but were not detected in the 16S rRNA sequences. Control experiments indicated that a bias against Haloferax sequences in the generation of the 16S rRNA gene library was unlikely, suggesting that Haloferax spp. readily form colonies, even though they were not a dominant group. Secondly, while the 16S rRNA gene library identified the SHOW group as a major component of the microbial community, no isolates of this group were obtained. This inability to culture members of the SHOW group remains an outstanding problem in studying the ecology of hypersaline environments.